Perceptions of lecturers on English as a primary medium of instruction at a selected university in South Africa - Munyaradzi, Juliet; Manyike, Tintswalo Vivian (Journal for Language Teaching, 2022)
In the current era of globalization, English medium instruction (EMI) in higher education in non-English speaking countries has gained prominence worldwide. The reasons for this include to increase institutions’ international visibility and competitiveness in the global market, to attract international students and to ensure graduates’ chances of international employability. In addition, more academic conferences are conducted in English and more prominent authors and academic journals choose to publish in English. Thus, many higher education systems privilege English in academic discourse. In light of this, this study explored lecturers’ perceptions of the recent implementation of English as a primary medium of instruction at a selected university in South Africa. Said’s and Bhabha’s postcolonial theories were used as theoretical lenses to inform the study and frame the data analysis. The sample chosen comprised three lecturers who are English Second Language (ESL) speakers. Data were gathered using classroom observations and individual semi-structured interviews. The results indicated that English as a primary medium of instruction diminished effective teaching and learning. The participants frequently code switched between African languages in the classroom. However, they acknowledged the role of English as a communication means in a multilingual context. It is recommended that students be adequately supported through the provision of adequately funded and quality English literacy programs and the implementation of African languages as media of instruction.